Role of histone methyltransferase SETDB1 in regulation of tumourigenesis and immune response - Zhao, Zhipeng; Feng, Lu; Peng, Xuerun; Ma, Tingnan; Tong, Rongsheng; Zhong, Lei (Frontiers in Pharmacology, 2022)
Epigenetic alterations are implicated in tumour immune evasion and immune checkpoint blockade (ICB) resistance. SET domain bifurcated histone methyltransferase 1 (SETDB1) is a histone lysine methyltransferase that catalyses histone H3K9 di- and tri-methylation on euchromatin, and growing evidence indicates that SETDB1 amplification and abnormal activation are significantly correlated with the unfavourable prognosis of multiple malignant tumours and contribute to tumourigenesis and progression, immune evasion and ICB resistance. The main underlying mechanism is H3K9me3 deposition by SETDB1 on tumour-suppressive genes, retrotransposons, and immune genes. SETDB1 targeting is a promising approach to cancer therapy, particularly immunotherapy, because of its regulatory effects on endogenous retroviruses. However, SETDB1-targeted therapy remains challenging due to potential side effects and the lack of antagonists with high selectivity and potency. Here, we review the role of SETDB1 in tumourigenesis and immune regulation and present the current challenges and future perspectives of SETDB1 targeted therapy.